Control interno de la gasolinera del sindicato parroquial de choferes profesionales de la isla de Bejucal en el periodo 2019-2020. - Naranjo Vinces, Neysi Nelly (2022)
The case study entitled "internal control of the gas station of the parish union of professional drivers of the island of bejucal in the period 2019-2020" was conducted with the purpose of preventing risks that directly affect the, finding the novelty that the mismanagement of internal control is being carried out within the administrative, tax and financial areas. For this reason, there is no adequate development in the economic area. Within the development we found valuable information regarding the deficiency of the financial statements since they are not audited by the general assembly in the period 2019, for this reason the present case focuses on carrying a good internal control and maintain the guidelines and be clear about the objectives of the company either by performing constant monitoring, the technique used in this case study was based on a survey conducted to the accounting staff to determine what are the affectations that the company presents and know its real situation.